2019
DOI: 10.1097/aln.0000000000002822
|View full text |Cite
|
Sign up to set email alerts
|

Pectoralis-II Myofascial Block and Analgesia in Breast Cancer Surgery

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Thoracic paravertebral block is the preferred regional anesthetic technique for breast cancer surgery, but concerns over its invasiveness and risks have prompted search for alternatives. Pectoralis-II block is a promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 85 publications
1
61
0
1
Order By: Relevance
“…Two systematic reviews (Hussain et al, 2019;Versyck et al, 2019) comparing the PEC block to standard care found similar results to ours with a reduction in pain scores and in 24 hr opioid consumption. These reviews also compared the PEC block to the parvertebral block and their results suggested that the PEC block was not inferior to the paravertebral block.…”
supporting
confidence: 84%
“…Two systematic reviews (Hussain et al, 2019;Versyck et al, 2019) comparing the PEC block to standard care found similar results to ours with a reduction in pain scores and in 24 hr opioid consumption. These reviews also compared the PEC block to the parvertebral block and their results suggested that the PEC block was not inferior to the paravertebral block.…”
supporting
confidence: 84%
“…Two meta‐analyses comparing PECS to paravertebral blocks reported similar results on pain reIief and analgesia consumption . A third meta‐analysis also demonstrated the efficacy of PECS blocks to reduce pain and morphine consumption when compared with no block or placebo .…”
Section: Resultsmentioning
confidence: 78%
“…36 Hussain N and colleagues undertook a systematic review and meta-analysis to provide evidence that pectoral nerve blocks could be a promising alternative to paravertebral block. 37 To the best of our knowledge, this study is the first to evaluate the efficacy and safety of co-administering PECS I, SIPB, and PSI block in patients undergoing MRM. In contrast to another prospective clinical trial, 30 our findings indicate that combining all three nerve blocks reduced NRS scores and morphine requirement compared to PECS I block and SIPB alone.…”
Section: Discussionmentioning
confidence: 97%
“…15 Thoracic paravertebral block is regarded as the priority option for regional anesthesia during breast cancer surgery; however, the invasive procedure requires excellent skill, experience, and deep puncturing. 16 PECS I involves local anesthetic injection between pectoralis major and minor muscle, and it is a controlled and reliable technique that intercepts the innervation of the medial and lateral pectoralis nerves originating from cervical and brachial plexuses. 17 SIPB, an inter-fascial approach between the serratus anterior muscle and external intercostal muscle or below serratus anterior muscle, was initially proposed as an alternative regional anesthetic technique that targets the lateral cutaneous branches of the thoracic intercostal nerves (TICN).…”
Section: Introductionmentioning
confidence: 99%